The Epidemic Prediction of Coronavirus disease 2019 Based on a SEIR(Susceptible-Exposed-Infected-Removed) Model Considering Population Migration between Wuhan and other Provinces in China. Issue 4 (January 2021) - Wang, Anran; Zhan, Ruobing; Yu, Fen; Mi, Jie; Gao, Kaiye
Abstract: As the first city detected the novel coronavirus in China, Wuhan was quarantined since Jan 23, 2020. The measure effectively prevented the epidemic spreading between provinces in China. This article proposes the SEIR infectious disease dynamics model introduced the inter-provincial migration factor, which is called the SEIRM model. The proposed model analyses the epidemic situation of 7 kinds of people when they can migrate freely between Wuhan and other provinces in China. Using the proposed model, we predict that until March 1st, 2020, the top five most severely epidemic-affected provinces are Hubei Province, Guangdong Province, Henan Province, Hunan Province, and Jiangxi Province; it is also predicted that more than 60.25 million people will be infected and approximately 837 thousand people will die due to this epidemic, which will exceed the medical resources load in China. According to our results, the population migration during the Spring Festival will quickly lead to a large-scale epidemic outbreak in China, which implies that locking down Wuhan and quarantine measures nationwide have a positive effect on China's epidemic prevention. Epidemic prevention measures will effectively prevent the spread of the epidemic, quickly restore social and economic order, and protect the health of the people of the country.